Determining the attitudes of university and high school students towards sports by structural equation modelling - Yucel, Ali Serdar; Korkmaz, Murat; Herguener, Gulten; Yaman, Cetin; Bal, Fatih; Kuyucu, Mihalis Michael (Sielae & Univ Coruna, Fac Filologia, 2024)
Sport is considered as an important service sector with its protective features for personal and public health, and developed countries regard sport as an indispensable part of their social life. The main purpose of this study is to assess factors affecting views of high school and university students towards sports. Within the scope of the study, the sample of the study is composed of 8546 students chosen with random method throughout Turkey. 5-point Likert scale consisting of 19 questions was used in order to determine views of the participants towards sports within the framework of the research. For analysing data, frequency analysis, reliability analysis and explanatory factor analysis were used in order to determine attitudes of students towards sports while structural equation model analyses were used in order to determine the relationship among the said factors regarding views towards sports. According to significance values of test statistics, all measured questions were statistically found significant for social- psychological attitude factor and physical mental attitude factor. According to the result of the model, there is a same-oriented and statistically significant relationship between social- psychological attitudes of students and their physical-mental attitudes. According to this result, when the views of students tend to be positive socially-psychologically towards sports, their physical-mental attitudes also become positive in parallel with this change. In line with the acquired result, it is necessary to demonstrate positive effects of sports on individuals socially, psychologically, physically and mentally in order to enable students to become more inclined to sports.
Determinación de las actitudes de los estudiantes universitarios y de bachillerato hacia el deporte mediante un modelo de ecuaciones estructurales
Keywords: sports; attitude; student; structural equation